Ordinary Christology Who Do You Say I Am? Answers From The Pews. - Christie, Ann. (Farnham : Ashgate Pub., 2012)
Ordinary Christology is defined as the account of who Jesus was/is and what he did/does that is given by Christian believers who have received no formal theological education. In this fascinating study Ann Christie analyses, and offers a theological appraisal, of the main christologies and soteriologies operating in a sample of ordinary churchgoers. Christie highlights the formal characteristics of ordinary Christology and raises questions about how we should respond to the beliefs about Jesus held by ordinary churchgoers.
8 Some Formal Characteristics of Ordinary ChristologyOrdinary Christology is Story-Shaped; Do Ordinary Believers 'Do Christology'?; Ordinary Christology and Affective Christology; On Not Learning Christological Dogma; Is Ordinary Christology Essentially Non-Cognitive?; 9 Living Christology; Engaging With the Story of Jesus; Difficulties of Engagement; The Story and Salvation; Is Jesus Really That Important?; Learning From Ordinary Christology; Bibliography; Index.
Description based on print version record.
Keywords: Religion; Jesus Christ -- Person and offices -- Miscellanea; Salvation -- Christianity -- Miscellanea; Theology, Doctrinal -- Popular works; RELIGION / Christian Theology / Christology; Electronic books